Distributed computer and communication networks : 18th International Conference, DCCN 2015, Moscow, Russia, October 19-22, 2015, revised selected papers /: 18th International Conference, DCCN 2015, Moscow, Russia, October 19-22, 2015, revised selected papers. ([2016]) - Unknown
No abstract available